O-014 The use of alternatives to clopidogrel in pipeline flow diversion. (23rd July 2017) - Atallah, E; Bekelis, K; Tjoumakaris, S; Rosenwasser, R; Jabbour, P
Abstract : Background: Thromboembolic complications continue to be encountered with PED despite the routine clopidogrel/aspirin anti-platelet therapy. Our study examined the safety and the efficacy of prasugrel and ticagrelor in the management of clopidogrel resistant patients treated for cerebral aneurysms. Methods: 437 consecutive patients were identified between January 2011 and May 2016. Patients allergic or having and it30% platelet-inhibition with a daily 75 mg of clopidogrel received 10 mg of prasugrel daily (n=20) or 90 mg of ticagrelor twice daily (n=2). The mean follow-up was 15.8 months (SD=12.4 months). The primary outcome was the modified Rankin Scale (mRS) registered before the discharge and at each follow-up visit. To control confounding we used multivariable mixed-effects logistic regression and propensity score conditioning. Results: Of 437 patients (mean of age 56.3 years; 62women [14, 2%]), 26 (5.9%) presented with an acute sub-arachnoid hemorrhage. 7 patients were lost to follow-up (1 from the prasugrel group). 1 patient was reported allergic to clopidogrel and prasugrel. All the 22 patients receiving prasugrel had a mRS&It=2 on their latest follow-up visit (mean=0.67; SD=1.15). In a multivariate analysis, clopidogrel did not affect the mRS on last follow-up, p=0.14. Multivariable logistic regression showed that clopidogrel was not associated with an increased long-term recurrence rate (odds ratio[OR], 0.17; 95%confidence interval [CI95%], 0.01–2.70; p=0.21) neither with an increased thromboembolic accident rate (OR, 0.46; CI95%, 0.12–1.67; p=0.36) nor with an increased hemorrhagic event rate (OR, 0.39; CI95%, 0.91–1.64; p=0.20). None of the patients receiving prasugrel deceased or had a long-term recurrence neither a hemorrhagic event, only 1 patient suffered from mild aphasia subsequent to a thromboembolic event. 3 patients on clopidogrel deceased during the study: (2)from acute SAH and (1)from intra-parenchymal hemorrhage. Clopidogrel was not associated with an increased mortality rate (OR, 2.18; CI95%, 0.11–43.27; p=0.61). The same associations were present in propensity score adjusted models. Conclusion: In a cohort of patients treated with PED, prasugrel (10 mg/day) and ticagrelor (90 mg twice/day) are safe alternatives to clopidogrel resistant, allergic or non-responders. Disclosures: E. Atallah: None. K. Bekelis: None. S. Tjoumakaris: None. R. Rosenwasser: None. P. Jabbour: None.